2016
DOI: 10.3909/riu0817
|View full text |Cite
|
Sign up to set email alerts
|

Isolated Left Ventricular Noncompaction Cardiomyopathy: A Transient Disease?

Abstract: Isolated left ventricular noncompaction is either a distinct cardiomyopathy or a morphologic trait shared by several different types of cardiomyopathies. Although there is no current gold standard for its diagnosis, cardiac imaging is the most commonly accepted modality. Described is a case of left ventricular noncompaction that resolved 2 years after the initial diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
(17 reference statements)
0
1
0
1
Order By: Relevance
“…Vinardell et al described the case of a woman with isolated LVNC who was managed by a guidelines-determined medical treatment, implantation of an internal cardioverter defibrillator, and resynchronization treatment; her complications resolved 2 years after the initial diagnosis with a normalization of LV volumes and ejection fraction and an almost complete resolution of the previously noted trabeculations. The authors concluded that non-compaction CM can either have a dynamic course or may be reversible, or that current morphologic criteria may occasionally misclassify a transient CM as non-compaction [ 93 ].…”
Section: Therapeutic Approachmentioning
confidence: 99%
“…Vinardell et al described the case of a woman with isolated LVNC who was managed by a guidelines-determined medical treatment, implantation of an internal cardioverter defibrillator, and resynchronization treatment; her complications resolved 2 years after the initial diagnosis with a normalization of LV volumes and ejection fraction and an almost complete resolution of the previously noted trabeculations. The authors concluded that non-compaction CM can either have a dynamic course or may be reversible, or that current morphologic criteria may occasionally misclassify a transient CM as non-compaction [ 93 ].…”
Section: Therapeutic Approachmentioning
confidence: 99%
“…Ainda não existe conhecimento exato da prevalência, porém estudos ecocardiográficos atingem 0,014%, sendo possível que esse número seja subestimado devido que a maioria são em hospitais terciários e paciente sem sintomas (Vinardell;Avila;Santana, 2016).…”
Section: Introductionunclassified